Radical evil : a philosophical interrogation - Bernstein, Richard J. (Polity Press, 2002)
At present, there is an enormous gulf between the visibility of evil and the paucity of our intellectual resources for coming to grips with it. We have been flooded with images of death camps, terrorist attacks and horrendous human suffering. Yet when we ask what we mean by radical evil and how we are to account for it, we seem to be at a loss for proper responses. Bernstein seeks to discover what we can learn about the meaning of evil and human responsibility. He turns to philosophers such as Kant, who coined the expression 'radical evil', as well as to Hegel and Schelling. He also examines more recent explorations of evil, namely the thinking of Freud and Nietzsche on the moral psychology of evil. Finally, he looks at the way in which three post-Holocaust thinkers - Emmanuel Levinas, Hans Jonas, and Hannah Arendt - have sought to come to grips with evil "after Auschwitz." Bernstein's primary concern throughout this challenging book is to enrich and deepen our understanding of evil in the contemporary world, and to emphasize the vigilance and personal responsibility required for combating it. "Radical Evil" will be essential reading for students and scholars of philosophy, social and political theory, and religious studies.